Gambaran Ultrasound Pada Ruptur Tendon Achiles - Fitriningsih, Mira; Septrila, Gladys (Universitas Kristen Krida Wacana, 2024)
Achilles tendon rupture is a condition where there is a tear in the Achilles tendon. Even though this tendon is the largest and strongest tendon, the Achilles tendon is the tendon that is most often damaged in the human body. This is often caused by sports activities and is often found in elderly men. 2,3 Ultrasound has an important role in diagnosing Achilles tendon rupture. This case report discusses a 63 year old man who experienced sudden pain in his ringht ankle during exercise. Then it appeared like a lump on the back of his leg. Then an ultrasound was performed and it was found that the Achilles tendon was discontinuous